Chest X-ray Appearance of COVID-19 Infection in Patong Hospital - โกยทรัพย์สิน สกันยา (Journal of Health Science of Thailand, 2021)
The purpose of this study was to collect chest radiographic findings of confirmed COVID-19 patients. This is a retrospective review of confirmed COVID-19 patients who were diagnosed and admitted in Patong Hospital, Phuket Province, Thailand, between January to July 2020. Patient demographics were reviewed and chest radiographs were assessed. This study included 78 confirmed COVID-19 patients: 60 patients (76.9%) had normal chest x-ray and 18 patients (23.1%) had abnormal x-ray findings. The majority of abnormal chest radiographs were the observation of ground glass and patchy opacities (10 cases, 55.6%); bilateral involvement (14 cases, 77.8%); middle zones (17 cases, 94.4%), lower zones (15 cases, 83.3%), and peripheral distribution (11 cases, 61.1%). Most of the chest radiographic findings in this study were consistent with previous studies in other countries.